Venture capital networks : a multilevel perspective - Bellavitis, Cristiano (Finance and financial management collection., 2018)
In the venture capital (VC) industry, firms often co-invest with other peers in syndicated deals. The process of syndication is a form of investment alliance that generates networks of VC firms and start-up companies. Despite the prominent role played by syndicates, extant entrepreneurship literature found contradicting evidence on the relationship between the practice of syndication and the performance of both the start-up and the investors. In fact, our understanding of the circumstances under which syndicates have the potential to boost performance, rather than hamper them, is still limited. Previous literature suggested that syndicates improve the access to resources for both the entrepreneurs and the VC partners. However, syndicates, as opposed to solo investments, carry agency costs such as free riding and conflicts of interests among co-investors. I investigate the role of syndicates on performance building upon network and alliance literature. Recent studies show that syndicates, networks, and alliances have the potential to be both an asset and a liability for the focal actor. This applies to the amount of connections that a firm has, the structure of its network, or the composition of the alliance. I apply a contingency perspective to investigate the boundary conditions under which syndication exerts a positive rather than a negative effect on performance. I test theoretical claims at three levels of analysis: at the start-up level, at the VC investors' level, and the syndicate level.